2020
DOI: 10.1097/iop.0000000000001760
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Orbital and Intracranial Abscesses in 17 Cases

Abstract: Purpose: To describe the demographics, clinical presentation, treatment, and outcomes of a rare cohort with simultaneous orbital and intracranial abscesses. Methods: A historical cohort study of 17 patients with simultaneous orbital and intracranial abscesses between 2010 and 2018 was performed. The demographics, location of abscesses, treatment, and outcomes of these patients were analyzed. Results: The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…To the best of the authors' knowledge, there have been 3 cases of OA managed nonsurgically reported in the literature. 15,16,41 Two were pediatric patients, including a 7-year-old girl with a small intraconal OA treated successfully with ceftriaxone and an 8-year-old boy with a superior OA and frontal epidural abscess discharged after 5 days of IV antibiotic therapy, both with limited additional case information. 15,41 The only reported adult OA patient successfully managed nonsurgically was a 54-year-old woman who developed an OA following sub-Tenon's injection of a steroid after laser photocoagulation for diabetic macular edema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of the authors' knowledge, there have been 3 cases of OA managed nonsurgically reported in the literature. 15,16,41 Two were pediatric patients, including a 7-year-old girl with a small intraconal OA treated successfully with ceftriaxone and an 8-year-old boy with a superior OA and frontal epidural abscess discharged after 5 days of IV antibiotic therapy, both with limited additional case information. 15,41 The only reported adult OA patient successfully managed nonsurgically was a 54-year-old woman who developed an OA following sub-Tenon's injection of a steroid after laser photocoagulation for diabetic macular edema.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,41 Two were pediatric patients, including a 7-year-old girl with a small intraconal OA treated successfully with ceftriaxone and an 8-year-old boy with a superior OA and frontal epidural abscess discharged after 5 days of IV antibiotic therapy, both with limited additional case information. 15,41 The only reported adult OA patient successfully managed nonsurgically was a 54-year-old woman who developed an OA following sub-Tenon's injection of a steroid after laser photocoagulation for diabetic macular edema. 16 She was treated with IV ciprofloxacin 500 mg twice daily, vancomycin 1 g twice daily, and metronidazole 80 mg twice daily, which achieved full infection resolution with sequelae of conjunctival and corneal scarring.…”
Section: Discussionmentioning
confidence: 99%